THE EFFECT OF DEMOGRAPHIC BONUS, HEALTH AND PHYSICAL CAPITAL ON ECONOMIC GROWTH IN INDONESIA - Arsyaf Tampubolon; Suwandy Purba (SEAN Institute, 2022)
This study aims to analyze the effect of demographic bonuses, health and physical capital on economic growth in several provinces of Indonesia. Using panel data for the period 2010 to 2019. The study uses panel data regression analysis of fixed effect models. The results showed that the level of health had a positive effect on economic growth in the provinces located on the islands of Sumatra and Sulawesi, Indonesia. Meanwhile, other factors from the demographic bonus and physical capital have not had an effect on economic growth in the provinces of Sumatra Island and Sulawesi Island, Indonesia.